Спрямований пошук протиракових агентів серед похідних [1,2,4]триазино[2,3-c]хіназоліну як один з напрямків реалізації стратегії по імпортозаміщенню хіміотерапевтичних препаратів - Коваленко, Сергій Іванович; Воскобойнік, Олексій Юрійович; Kovalenko, S. I.; Voskoboynik, O. Yu. (My University, 2018)
Імпортозаміщення лікарських препаратів, зокрема протипухлинної дії є важливою складовою стратегії розвитку медичної галузі, що серед іншого передбачає активізацію наукових розробок, метою яких є створення інноваційних лікарських препаратів. Мета. Представлена робота є узагальненням власного досвіду з планування та реалізації проектів по створенню синтетичних сполук з вираженою протираковою дією на основі похідних [1,2,4]триазино[2,3-c]хіназоліну та продуктів їх структурної модифікації. Результати. Нами було проведено планування роботи, яке дозволило визначити наступні етапи досліджень: вибір напряму досліджень, вибір класу органічних сполук як об’єктів фармакологічних досліджень, вибір підходів до конструювання потенційних біоактивних молекул, синтез потенційних біоактивних молекул, прескринінг протиракової активності, первинний скринінг на наявність протиракової дії синтезованих сполук, аналіз одержаних результатів первинного скринінгу, спрямована хімічна модифікація одержаних сполук, поглиблені дослідження протиракової дії. В результаті реалізації проекту були одержані сполуки-лідери та додаткова інформація для подальших досліджень. Import-substitution of medicines, in particular antitumor activity, is an important component of the strategy for medical industry development, and among other, provides for the scientific research activation aimed at the creation of innovative medicines. Aim. The presented work is a generalization of own experience in planning and realization of projects on creation of synthetic compounds with significant anticancer activity based on [1,2,4]triazino[2,3- c]quinazoline derivatives and products of their structural modification. Results. We conducted work planning, which allowed us to identify the following stages of the study: the choice of the research direction, the choice of the class of compounds as objects of pharmacological research, the choice of approaches to the design of potential bioactive molecules, the biological activity pre-screening, the primary screening for anticancer activity of synthesized compounds, analysis of obtained data, profound study of the anticancer activity. The search of novel anticancer agents was conducted among the series of [1,2,4]triazino[2,3-c]quinazolines and related compounds, that may be obtained by modification of substituted 3-(2-aminophenyl)-6-R-1,2,4-triazino-5(2H)- ones. Considering to the structure similarity of studied compounds to the well-known anticancer drugs – 4-anilinoquinazolines, they may reveal tyrosine-kinase inhibiting effects and as result anticancer activity. The biological activity pre-screening using molecular docking study and bioluminescence inhibition model, in vitro study of FGFR1-inhibiting activity and in vitro study of anticancer activity were conducted for synthesized compounds. As a result of the project, lead-compounds were obtained, as well, as additional information for further studies. Conclusions. One of the possible variants for the research conduction aimed at creating of innovative anticancer drugs has been developed. The presented strategy can be used by small groups of researchers in universities, research institutions and commercial pharmaceutical enterprises.
Purposeful search of anticancer agents among [1,2,4]triazino[2,3-c] quinazolines derivatives as one of the directions in realization the import substitution strategy of chemotherapy medicines
Keywords: протипухлинні лікарські препарати; імпортозаміщення; планування; дослідження; antineoplastic drugs; import substitution; planning; research